2018
DOI: 10.3389/fimmu.2018.02018
|View full text |Cite
|
Sign up to set email alerts
|

Fra2 Overexpression in Mice Leads to Non-allergic Asthma Development in an IL-13 Dependent Manner

Abstract: Background: Asthma is a complex chronic inflammatory disease characterised by airway inflammation, remodelling and hyperresponsiveness (AHR). Members of the AP-1 transcription factor family play important roles in the activation of the immune system and the control of cellular responses; however, their role in the development of asthma has not been well studied. We aimed to investigate the role of the lesser known AP-1 family member, Fra2 in experimental asthma.Methods: Phenotypic characterisation and gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
5
28
0
1
Order By: Relevance
“…In the next step, inflammatory cells in the BALF of mice were quantified and analysed by flow cytometry. As previously described, Fra-2 TG have increased numbers of inflammatory cells in the BALF, predominately consisting of eosinophils, T-lymphocytes and B-lymphocytes (figure 6a) [23]. While anakinra treatment did not lead to changes in inflammatory cell numbers in WT mice, increased amounts of T-cells, B-cells and eosinophils in Fra-2 TG mice treated with anakinra were observed (figure 6a).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In the next step, inflammatory cells in the BALF of mice were quantified and analysed by flow cytometry. As previously described, Fra-2 TG have increased numbers of inflammatory cells in the BALF, predominately consisting of eosinophils, T-lymphocytes and B-lymphocytes (figure 6a) [23]. While anakinra treatment did not lead to changes in inflammatory cell numbers in WT mice, increased amounts of T-cells, B-cells and eosinophils in Fra-2 TG mice treated with anakinra were observed (figure 6a).…”
Section: Resultssupporting
confidence: 67%
“…An additional confounding factor is the effect of IL-1 on inflammation in this mouse model. We previously reported that inflammation in Fra-2 TG mice is predominately Th2 driven with strong eosinophilia [23]. Upon treatment with anakinra, Fra-2 TG mice developed even higher eosinophilia (Th2 response), whereas no effects were observed in WT mice, indicating that the complex immunomodulatory actions of IL-1 strongly depend on the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…To comprehensively describe the inflammatory cell kinetics following bleomycin treatment, we assembled and conjointly analyzed historical FCM data from 15 independent experiments, which resulted in 159 bronchoalveolar lavage fluid (BALF) and 144 lung tissue samples ( Table S1 ). Using standard gating strategies ( Misharin et al., 2013 ; Biasin et al., 2017 ; Nagaraj et al., 2017 ; Gungl et al., 2018 ), a total of 16 cell populations covering the main myeloid and lymphoid cell types ( Table 1 ) were identified ( Figure 1 C). The aggregation of historical experiments inherently led to an unbalanced [ Box 1 ] experimental design ( Table S1 ), which was handled by robust statistical methods [ Box 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is intriguing that IL-13 blockade modulates several aspects of different experimental models of allergic asthma (Laporte et al, 2001; Walter et al, 2001; Komai et al, 2003; Munitz et al, 2008; Chen et al, 2013; Ma et al, 2013; Chachi et al, 2017). Moreover, recent results demonstrate that anti-IL-13 antibody improves bronchial hyperresponsiveness and mucus production in a mouse model of non-allergic asthma (Gungl et al, 2018). These positive experimental results contrast with negative results in the treatment of asthmatic patients with different anti-IL-13 mAbs (tralokinumab and lebrikizumab) (Piper et al, 2013; Brightling et al, 2015; Hanania et al, 2016; Panettieri et al, 2018; Russell et al, 2018; Busse et al, 2019).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In a novel mouse model of non-allergic asthma overexpression of the activator protein-1 (AP-1) subunit Fra2, caused airway inflammation with IL-13 overexpression, BAL eosinophilia, mucus hyperproduction, AHR, and peribronchial collagen deposition (Gungl et al, 2018). Administration of anti-IL-13 antibody markedly decreased STAT6 phosphorylation in the lung, BAL eosinophilia, and goblet cell hyperplasia.…”
Section: Introductionmentioning
confidence: 99%